A novel framework for supporting the design of moving block train control system schemes. (September 2014) - Wang, Haifeng; Tang, Tao; Roberts, Clive; Gao, Chunhai; Chen, Lei; Schmid, Felix
A moving block philosophy is increasingly being implemented as part of communications-based train control (CBTC) systems in mass transit operations. Due to its complexity and safety criticality, it is difficult to develop formal methods to support the design of specific schemes. An innovative framework, based on topology mathematics, for supporting CBTC moving block system development is proposed in this paper. Within the new framework, the moving block train control logic is transformed into topological spaces representing the movement authority for trains. Using this approach, the verification of logic and safety properties can be performed by automatic assessment of the topological space. Within the paper the essential characteristics of moving block systems, train behaviour and static track-side infrastructure are analysed. As a result of this analysis, topological units are formed to represent train movement trajectory and standard railway network elements. Four calculation methods: dividing, trimming, covering and integrating, are described as standard unit operations. Finally, a case study is implemented to demonstrate how the method is advantageous for CBTC scheme layout development. It is found that the approach is able to bridge the gap between traditional, highly abstracted, formal methods and the specific safety-critical railway scheme designs.